Análise geoecológica como subsídio ao planejamento ambiental em área susceptível à desertificação no semiárido cearense - Teixeira, Nágila Fernanda Furtado (2023)
The historical process of use and occupation of the semi-arid region of Ceará is characterized by the development of economic activities, mainly agricultural practices that exploit natural resources to the maximum. This fact promotes negative impacts, compromises environmental quality, causes strong ecological imbalances, and leads to environmental degradation and economic and social harm in the semi-arid region. Therefore, it is necessary to conduct environmental studies aimed at analyzing the geo-environmental and socio-economic framework, identifying, delimiting, and assessing environmental degradation, and proposing planning actions that allow for the mitigation of impacts and promote community development based on sustainability principles. This work aims to conduct a geoecological analysis to support environmental planning in an area susceptible to desertification in the semi-arid region of Ceará, with the investigative focus on the municipality of Pentecoste, located in the central-northern sector of the state of Ceará. The municipality covers an area of 1,378.3 km2 and is divided into four districts: Pentecoste, Matias, Porfírio Sampaio, and Sebastião de Abreu. Supported by the theoretical and methodological foundation of Landscape Geoecology, the research is divided into the following stages: organization and inventory, analysis, diagnosis, and proposal, which allowed for the detailed examination of geo-environmental characteristics such as geology, geomorphology, soil, climate, hydrology, and vegetation. Socioeconomic aspects including demographics, economy, education, health, sanitation, and culture were also considered. The municipality was delineated, compartmentalized, and analyzed into six geoecological units: Pentecoste Sertaneja Depression, Curu River Floodplain, Canindé River Floodplain, Maracajá Mountain Range, Santa Luzia Mountain Range, and Serrinha Mountain Range. The study emphasized the description of land use, potentials, limitations, and the five Geobiophysical Desertification Indicators (IBGD): porosity of lithotypes (IBGD 1); slope (IBGD 2); soil thickness (IBGD 3); soil erosion (IBGD 4); and vegetation cover (IBGD 5) for each of the six geoecological units. Finally, an environmental zoning proposal was developed to ensure the conservation of natural resources and the community development of the municipality, with the determination of zones: Permanent Preservation, Environmental Conservation, and Environmental Recovery. In conclusion, this study contributes to the scientific knowledge of the semi-arid environment by integrating qualitative, secondary, and primary data with geoprocessing techniques, generating data to support the analysis of the geoecological dynamics and desertification in Pentecoste.